2021
DOI: 10.1177/1358863x20984831
|View full text |Cite
|
Sign up to set email alerts
|

Gait changes after supervised exercise training in patients with symptomatic lower extremity peripheral artery disease

Abstract: This study aimed to investigate the effects of supervised exercise training (SET) on walking performance and spatiotemporal gait changes in patients with symptomatic lower extremity peripheral artery disease (PAD). In this single-arm prospective nonrandomized cohort study, patients with Fontaine stage II PAD following a 3-month SET program were included. Before and after SET, a constant-load treadmill test was performed to determine the pain-free and maximal walking distances (PFWD and MWD, respectively). Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 43 publications
2
35
1
Order By: Relevance
“…The Angiofit study is a longitudinal observational cohort of symptomatic patients (Fontaine stage II) participating in multimodal SET with stable uni- or bilateral lower limb claudication and resting ankle-brachial index (ABI) ≤ 0.9 or decreased post-exercise ABI > 20%. We recently showed that our clinical multimodal SET is effective in improving walking performance and quality of life [ 18 , 19 , 20 ] and that these improvements are maintained up to 12 months follow-up in patients with symptomatic PAD [ 20 ]. Compared to these previous observations [ 18 , 19 , 20 ], in the present study we included all patients participating in our clinical SET program up to 2020, having performed walking tests (treadmill and 6 min) and self-perceived HRQoL questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Angiofit study is a longitudinal observational cohort of symptomatic patients (Fontaine stage II) participating in multimodal SET with stable uni- or bilateral lower limb claudication and resting ankle-brachial index (ABI) ≤ 0.9 or decreased post-exercise ABI > 20%. We recently showed that our clinical multimodal SET is effective in improving walking performance and quality of life [ 18 , 19 , 20 ] and that these improvements are maintained up to 12 months follow-up in patients with symptomatic PAD [ 20 ]. Compared to these previous observations [ 18 , 19 , 20 ], in the present study we included all patients participating in our clinical SET program up to 2020, having performed walking tests (treadmill and 6 min) and self-perceived HRQoL questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that our clinical multimodal SET is effective in improving walking performance and quality of life [ 18 , 19 , 20 ] and that these improvements are maintained up to 12 months follow-up in patients with symptomatic PAD [ 20 ]. Compared to these previous observations [ 18 , 19 , 20 ], in the present study we included all patients participating in our clinical SET program up to 2020, having performed walking tests (treadmill and 6 min) and self-perceived HRQoL questionnaire. Exclusion criteria are inability to participate in SET three times weekly, critical limb ischemia, and cardiac contraindication to exercise.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The multimodal SET consisted of three 50-min sessions per week over a 3-month period (for a total of 36 sessions) and was coordinated by a vascular physician, and all sessions were supervised by a clinical exercise physiologist specialist in vascular rehabilitation [16,17].…”
Section: Multimodal Supervised Exercise Training Programmentioning
confidence: 99%